APPROACHES OF THE ASIAN DEVELOPMENT BANK TO SELF-EVALUATION OF OPERATIONAL EFFECTIVENESS: OPPORTUNITIES OF APPLICATION IN THE VNESHECONOMBANK OF RUSSIA - S. Matveevskiy (Вестник университета)
The financial condition of Russia’s Vnesheconombank (further - VEB) in recent years is characterized by a significant amount of non-performing assets, problems with funding, and large external debt. In this connection, the VEB can benefit from the experience of evaluating the effectiveness of multilateral development banks, in particular, the Asian Development Bank (further - ADB). The analysis of the assessment of the effectiveness of the activities of the ADB, carried out by the bank itself, was conducted, an evaluation methodology based on the integrated use of economic, financial, and «physical» indicators was identified. The recommendations of the VEB have been prepared, which will allow it to speed up the solution of current financial problems and to make better use of available resources.